Youth and Social Class : Enduring Inequality in the United Kingdom, Australia and New Zealand - France, Alan; Roberts, Steven (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book addresses the recent marginalisation of class theory in youth sociology. The authors argue for the importance of reinstating class analysis as central to understanding young people's lives in the United Kingdom, Australia and New Zealand. Their analysis recognises that in periods of social change, class relationships and processes can and do get reconfigured, but by drawing on the work of Pierre Bourdieu, they show that class, while being dynamic, remains core to shaping the everyday lives of young people. Students and scholars across a range of areas including the sociology of youth, sociology of education, social work and social policy will find this book of interest.
Keywords: Social sciences.; Social structure.; Social inequality.; Childhood.; Adolescence.; Social groups.; elektronické knihy; electronic books